2021
DOI: 10.1002/hbe2.271
|View full text |Cite
|
Sign up to set email alerts
|

Parent reports of children's parasocial relationships with conversational agents: Trusted voices in children's lives

Abstract: With the rise of smart devices in the 21 st century, children are increasingly engaged in socially contingent interactions with conversational agents such as Alexa, Google Assistant, and Siri. Using an online parent survey, young children's verbal interactions (parasocial interactions) and emotional relationships (parasocial relationships) with conversational agents were examined in a naturalistic study. A total of 92 parents responded to the survey, 70 of whom qualified because they had a conversational agent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 46 publications
(102 reference statements)
0
7
0
Order By: Relevance
“…Parasocial interaction refers to a kind of psychological relationship that users experience during conversations with AIPA ( Jang, 2020 ). The user may engage in a parasocial interaction with AIPA to request counseling or talk about his/her mind ( Hoffman et al., 2021 ). In particular, as the time to stay at home to prevent COVID-19 has increased recently, users have interacted with AIPA to mitigate mental damage ( Miner et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Parasocial interaction refers to a kind of psychological relationship that users experience during conversations with AIPA ( Jang, 2020 ). The user may engage in a parasocial interaction with AIPA to request counseling or talk about his/her mind ( Hoffman et al., 2021 ). In particular, as the time to stay at home to prevent COVID-19 has increased recently, users have interacted with AIPA to mitigate mental damage ( Miner et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, our study contributes to the literature by showing how today’s children systematically disentangle the ontological dimensions of psychology and intelligence when conceptualizing entities of distinct kinds in their home and childhood environments. But, as previous research has also shown, this does not mean children entirely refrain from using psychological qualities when conceptualizing technological entities, such as DVAs (e.g., Garg and Sengupta 2020 ; Girouard‐Hallam et al 2021 ; Hoffman et al 2021 ), smart toys (e.g., Turkle 2017 ), or robots (e.g., van Straten et al 2020 ). However, this study was able to show that, across a broad range of technological and organically living entities, children’s relative ontological conceptualisation patterns (in terms of relative deviation patterns from the sample mean) still tend to discriminate more rigorously on the basis of psychology and biology, and less on the basis of intelligence.…”
Section: Discussionmentioning
confidence: 98%
“…Accordingly, older children’s improving understanding of friendship may have helped them recognize that the human would be more likely to know personal information about the experimenter because she was her friend. At the same time, because young children are more likely to form parasocial relationships with nonhuman entities than older children, and parent reports suggest that they do so with digital voice assistants (Hoffman et al, 2021), they may have been more likely than older children to view the voice assistant as a source of personal information.…”
Section: Discussionmentioning
confidence: 99%